Asymmetric majority pillage games - Manfred Kerber; Colin Rowat; Naoki Yoshihara (University of Massachusetts, Department of Economics, 2019)
This paper studies pillage games (Jordan in J Econ Theory 131.1:26-44, 2006, "Pillage and property"), which are well suited to modelling unstructured power contests. To enable empirical test of pillage games' predictions, it relaxes a symmetry assumption that agents' intrinsic contributions to a coalition's power is identical. In the three-agent game studied: (i) only eight configurations are possible for the core, which contains at most six allocations; (ii) for each core configuration, the stable set is either unique or fails to exist; (iii) the linear power function creates a tension between a stable set's existence and the interiority of its allocations, so that only special cases contain strictly interior allocations. Our analysis suggests that non-linear power functions may offer better empirical tests of pillage game theory.
Keywords: C71; D51; P14; 330; power contests; core; stable sets